Patient‐reported outcomes in relapsed/refractory multiple myeloma treated with melflufen plus dexamethasone: analyses from the Phase II HORIZON study. (21st October 2021) - Larocca, Alessandra; Leleu, Xavier; Touzeau, Cyrille; Bladé, Joan; Paner, Agne; Mateos, María‐Victoria; Cavo, Michele; Maisel, Christopher; Alegre, Adrían; Oriol, Albert; Raptis, Anastasios; Rodriguez‐Otero, Paula; et al.
Summary: Relapsed/refractory multiple myeloma (RRMM) is known to have a high burden of disease and complications associated with refractoriness to prior lines of therapy. Severe pain and fatigue symptoms and impairments in physical and emotional functioning have been strongly linked to reduced health‐related quality of life (HRQoL) in patients with RRMM. Assessment of patient reported‐outcome measures from the pivotal, Phase II HORIZON study (OP‐106; NCT02963493) in patients with RRMM ( n = 64) demonstrated that melphalan flufenamide (melflufen) plus dexamethasone treatment preserved HRQoL. Patients had clinically meaningful improvements, even after eight treatment cycles, in relevant scales such as global health status/QoL, physical functioning, emotional functioning, pain, and fatigue. Patients with triple‐class–refractory disease ( n = 50) displayed similar improvements. Patient‐reported outcome deterioration was delayed for a substantial amount of time in patients who experienced a response to melflufen plus dexamethasone treatment relative to patients who did not experience a response. These findings support the notion that treatment with melflufen plus dexamethasone may sustain or improve HRQoL over time in patients with RRMM, including in patients with triple‐class–refractory disease for whom outcomes are generally worse. The clinical benefits observed in patients from the HORIZON trial are encouraging and supportive of translation into real‐world practice.